Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Adis Dimension Footwear - Anida Fauziyah; Karsikah (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This research is a quantitative study. The purpose of this study is to determine how leadership and work motivation affect the performance of employees at PT. Adis Dimension Footwear. The population and sample of employees used are 120 employees and the sample used is 120 employees. The data collection technique used is SPSS software which will be used for data analysis. The data analysis techniques include multiple linear regression, partial t-test, simultaneous F-test, and determination coefficient test. The research data was collected through questionnaires and analysed using SPSS 25. The research results show that leadership has a positive and significant effect on employee performance. Work motivation has also been shown to have a positive and significant effect on employee performance. Furthermore, leadership and work motivation simultaneously have a positive and significant effect on employee performance.